The effects of reciprocity, type of relationship, and culture on relationship processes - Gertrude C. Ah Gang @ Grace; Stukas, Arthur A. (Penerbit Universiti Kebangsaan Malaysia, 2015)
Equity theory suggests that perceiving equity leads to better relationship outcomes than perceiving inequity. However, cultural and relationship differences in tolerance for inequity have been found, suggesting that those from more individualistic cultures may have less tolerance for inequity with friends than those from more collectivistic cultures, with the latter group discriminating more clearly in their reactions to friends and strangers. In our first study, Kadazandusun (N=282) and Australian (N=255) participants evaluated their actual reciprocity in social support with a close friend. In our second study, 103 South East Asians and 128 Australians were randomly assigned to respond to a scenario presenting equity or inequity (underbenefit or overbenefit) with either a close friend or stranger. Study 1 found that participants from both cultures reported reduced desires for future interaction, positive feelings and closeness when they experienced under-benefit as compared to over-benefit or equity. In Study 2, participants from both cultures also reported reduced desires for future interaction, positive feelings and trust when there was inequity and reported a more negative reaction to a stranger than a close friend. These findings are consistent with equity theory and support its cross-cultural applicability.